High-dose Neural Stem Cell Radiation May Not Improve Survival in Glioblastoma. Issue 6 (June 2017) - Achari, R.; Arunsingh, M.; Badgami, R.K.; Saha, A.; Chatterjee, S.; Shrimali, R.K.; Mallick, I.; Arun, B.
Abstract: Aims: To evaluate the effect of radiotherapy dose-volume parameters of neural stem cell (NSC) compartment on progression-free survival (PFS) and overall survival after post-resection chemoradiation in newly diagnosed glioblastoma. Materials and methods: Sixty-one patients with unifocal glioblastoma were included. Ipsilateral (NSC_Ipsi), contralateral (NSC_Contra) and combined NSC (NSC_Combined) were contoured on radiotherapy planning computerised tomography datasets. NSC dose-volume parameters were correlated with PFS and overall survival. Serial magnetic resonance imaging scans were assessed to understand the frequency of pre- and post-treatment involvement of the NSC by contrast enhancing lesions (CELs). Results: Baseline involvement of NSC with CELs was seen in 67.2% and 95.9% had CELs and FLAIR abnormalities at progression. With a median follow-up of 14.1 months (interquartile range 9.4–20.6 months), median PFS and overall survival were 14.5 (95% confidence interval 11.6–17.5) and 16.2 (95% confidence interval 13.3–19.2) months, respectively. Poor Eastern Cooperative Oncology Group performance score, advanced recursive partitioning analysis class, unmethylated O6-methylguanine methyltransferase (MGMT) status, higher than median of mean NSC_Ipsi dose were associated with significantly inferior PFS and overall survival on univariate analysis. On multivariate analysis, unmethylated MGMT status, higher than median of mean doses to NSC_Ipsi and poor compliance to adjuvant temozolomide were independent predictors of inferior survival. Conclusions: In this cohort, 67.2% of newly diagnosed glioblastoma patients had NSC involved with CELs at presentation and 95.9% at progression. This might be an imaging surrogate of the current notion of gliomagenesis and progression from NSC rests. A high radiation dose to NSC_Ipsi was significantly associated with inferior survival. This could be a function of larger tumours and planning target volumes in those with pre-treatment NSC involvement. Methylated MGMT and good compliance to adjuvant temozolomide were independent predictors of better survival. Until further evidence brings hope for glioblastoma, elective, partial NSC irradiation remains experimental. Highlights: Radiation dose to neural stem cells and survival in glioblastoma has been analysed. Increased ipsilateral stem cell radiation dose was detrimental to survival. Elective neural stem cell radiation in glioblastoma remains experimental.